Genotypic and phenotypic analysis of 396 individuals with mutations in Sonic Hedgehog - Solomon, Benjamin; Gaspar, Harald (Journal of medical genetics, 2012)
Background: Holoprosencephaly (HPE), the most common malformation of the human forebrain, may result from mutations in over 12 genes. Sonic Hedgehog (SHH) was the first such gene discovered; mutations in SHH remain the most common cause of non-chromosomal HPE. The severity spectrum is wide, ranging from incompatibility with extrauterine life to isolated midline facial differences. Objective: To characterise genetic and clinical findings in individuals with SHH mutations. Methods: Through the National Institutes of Health and collaborating centres, DNA from approximately 2000 individuals with HPE spectrum disorders were analysed for SHH variations. Clinical details were examined and combined with published cases. Results: This study describes 396 individuals, representing 157 unrelated kindreds, with SHH mutations; 141 (36%) have not been previously reported. SHH mutations more commonly resulted in non-HPE (64%) than frank HPE (36%), and non-HPE was significantly more common in patients with SHH than in those with mutations in the other common HPE related genes (p<0.0001 compared to ZIC2 or SIX3). Individuals with truncating mutations were significantly more likely to have frank HPE than those with non-truncating mutations (49% vs 35%, respectively; p=0.012). While mutations were significantly more common in the N-terminus than in the C-terminus (including accounting for the relative size of the coding regions, p=0.00010), no specific genotype―phenotype correlations could be established regarding mutation location. Conclusions: SHH mutations overall result in milder disease than mutations in other common HPE related genes. HPE is more frequent in individuals with truncating mutations, but clinical predictions at the individual level remain elusive.
Gesehen am 24.07.2018